TINDAKAN WANPRESTASI OLEH NASABAH BERINISIAL RS PADA PT. BANK PEMBIAYAAN RAKYAT SYARIAH AMANAH UMMAH PUSAT: Tort Actions By A Customer With The Initials RS At PT. Bank Pembiayaan Rakyat Syariah Amanah Ummah Pusat - Bintang Nugraha Putra; Arif Wicaksana (AMICUS CURIAE, 2025)
The Murabahah Agreement is one of the contracts implemented in Sharia banking where the contract is carried out using a buying and selling system to obtain a profit by adhering strictly to the principles established by Islamic teachings. In this case, the contract executed between PT. Bank Pembiayaan Rakyat Syariah Amanah Ummah Pusat with a customer with the initials RS which creates a legal relationship, namely the existence of rights and obligations for each party. However, it cannot be easy to fulfill what has been agreed upon in the Murabahah agreement, and of course, with this, some problems arise, namely default or broken promises. This default is a situation where one party does not carry out the obligations he has agreed to. In this research, the customer with the initials RS was correct in acts of default or breaking promises by making installment payments and carrying out provisions that were prohibited in the Murabahah agreement that he had agreed to with PT. Bank Pembiayaan Rakyat Syariah Amanah Ummah Pusat.